A low dielectric constant metal-clad laminate and circuit board

CN224898291UActive Publication Date: 2026-10-27NINGBO TURBULENCE ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202521271098.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2026-10-27
Estimated Expiration
2035-06-20

AI Technical Summary

Technical Problem

[0003]然而,现有技术中,普通基板一般包括以环氧树脂、聚苯醚树脂、碳氢树脂、BT树脂、聚四氟乙烯中的一种或几种为主体树脂的基底、以及用于粘接基底的以环氧树脂为主体的FR4粘结片,其中基底的介电常数一般大于2.10,FR4粘结片的介电常数一般大于3.5,加上FR4粘结片在结构及材料组成上也未进行过多的优化和改进,导致普通基板的介电常数与介电损耗普遍较高,即使是经过改性的低损耗FR4基板,普遍地其介电常数仍大于3.8,介电损耗仍大于0.007,完全达不到低介电常数(DK<2.0)、低介电损耗(Df<0.005)的要求

Benefits of technology

本实用新型的低介电常数覆金属箔层压板和由低介电常数覆金属箔层压板加工而成的电路板,满足低介电常数DK<2.0、低介电损耗Df<0.005、金属箔剥离强度>3 lbs/inch的性能要求,能降低高频信号在通过低介电低损耗粘结层与发泡塑料层界面产生的折射与反射损失,能满足金属箔与基材的牢固粘接与粘接的长期可靠性,即不出现因为长期使用或使用环境影响下出现金属箔与基材分层或金属箔鼓泡的情况;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224898291U_ABST
    Figure CN224898291U_ABST
Patent Text Reader

Abstract

The utility model discloses a kind of low dielectric constant metal-clad laminate and circuit board, comprising: at least one metal foil, at least one low dielectric low-loss adhesive layer, at least one foamed plastic layer, at least one low dielectric low-loss adhesive layer is arranged between metal foil and foamed plastic layer;Metal foil, low dielectric low-loss adhesive layer and foamed plastic layer are laminated into laminar structure, and low dielectric low-loss adhesive layer has reinforcing layer composed of one or two of polytetrafluoroethylene film, polytetrafluoroethylene ceramic composite film.The metal-clad laminate meets the performance requirements of low dielectric constant DK<2.0, low dielectric loss Df<0.005, metal foil peel strength>3lbs / inch, can reduce high-frequency signal refraction and reflection loss between different layers, while meeting the firm adhesion of metal foil and substrate and the long-term reliability of adhesion, i.e. metal foil and substrate delamination or metal foil blistering do not occur due to long-term use or use environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to communication and antenna applications in the aerospace field, and in particular to a low dielectric constant metal foil laminate and circuit board. Background Technology

[0002] Antennas are key components of communication and radar systems, and antenna arrays fabricated using printed circuit boards (PCBs) are widely used due to their low cost, ease of fabrication, and high precision. However, the design, structure, size, and performance of an antenna are closely related to the dielectric properties of the PCB substrate material. For example, a low dielectric constant (DK<2) can effectively increase antenna bandwidth and reduce signal delay, while low dielectric loss (Df<0.005) can improve antenna gain and energy efficiency. Therefore, reducing the dielectric constant and dielectric loss of the substrate is an important research topic in this field.

[0003] However, in existing technologies, ordinary substrates generally consist of a base made primarily of one or more of the following resins: epoxy resin, polyphenylene ether resin, hydrocarbon resin, BT resin, and polytetrafluoroethylene (PTFE), and an FR4 adhesive sheet made primarily of epoxy resin for bonding the base. The dielectric constant of the base is generally greater than 2.10, and the dielectric constant of the FR4 adhesive sheet is generally greater than 3.5. Furthermore, the structure and material composition of the FR4 adhesive sheet have not been significantly optimized or improved, resulting in generally high dielectric constants and dielectric losses in ordinary substrates. Even modified low-loss FR4 substrates generally still have dielectric constants greater than 3.8 and dielectric losses greater than 0.007, failing to meet the requirements for low dielectric constant (DK < 2.0) and low dielectric loss (Df < 0.005). Simultaneously, existing ordinary substrates are also difficult to isolate from the influence of the external environment, which to some extent reduces the overall weather resistance of the circuit board.

[0004] In addition, some adhesive sheets have poor weather resistance. Under some extreme environmental conditions, such as severe high and low temperature cycling or long-term humid conditions (epoxy resin or PI resin adhesives have high water absorption rates), they are prone to bonding failure, resulting in bulging or even delamination of the metal foil. Utility Model Content

[0005] The main objective of this invention is twofold: firstly, to provide a low-dielectric-constant metal-clad laminate to at least partially solve the aforementioned problems; and secondly, to provide a circuit board made from the aforementioned low-dielectric-constant metal-clad laminate, which enables antennas fabricated using this circuit board to effectively increase antenna bandwidth and reduce signal delay, while also improving antenna gain and energy efficiency.

[0006] As a first aspect of this utility model, in order to achieve the above-mentioned objective, the low dielectric constant metal foil laminate provided by this utility model includes: at least one metal foil, at least one low dielectric low loss adhesive layer, and at least one foamed plastic layer, wherein at least one low dielectric low loss adhesive layer is disposed between the metal foil and the foamed plastic layer; the metal foil, the low dielectric low loss adhesive layer and the foamed plastic layer are stacked to form a layered structure, wherein the low dielectric low loss adhesive layer has a reinforcing layer composed of one or two of polytetrafluoroethylene film and polytetrafluoroethylene ceramic composite film.

[0007] Preferably, the metal foil includes one or more of copper foil, aluminum foil, stainless steel, and embedded copper foil.

[0008] Preferably, the thickness of the metal foil is between 8 micrometers and 200 micrometers.

[0009] Preferably, the dielectric constant DK of the layered structure is <2.0, the dielectric loss Df is <0.005, and the metal foil peel strength is >3 lbs / inch.

[0010] Preferably, the dielectric constant of the low-dielectric-low-loss adhesive layer is between 2.0 and 2.8, and the dielectric loss Df < 0.004.

[0011] Preferably, the dielectric constant of the foamed plastic layer is less than 2.0.

[0012] In existing technologies, the dielectric constant of ordinary adhesive layers is often relatively high (e.g., the dielectric constant of ordinary epoxy resin adhesive layers is 3.7–4.0, that of thermosetting PI adhesive layers is 4.0, and that of modified polyphenylene ether and TAIC system adhesive layers is 3.2–3.5), while the dielectric constant of foamed materials is less than 2.0. Therefore, when using adhesive layers with high dielectric constants in existing technologies, the actual test results of microwave devices often differ significantly from the simulation results. For example, when using foamed plastic to fabricate Luneburg lenses, epoxy resin bonding leads to the aforementioned problems, mainly because the large difference in dielectric constant between the adhesive layer resin in existing technologies and the foamed plastic layer in this application results in microwave refraction and reflection losses. (YAN Xiulin, SHI Yunqi, ZHU Lina. Design of Luneburg Lens Antenna Based on Novel FoamMaterials[J]. Journal of Electronics & Information Technology, 2022, 44(12):4111-4115. doi: 10.11999 / JEIT220569). Therefore, this application reduces the refraction and reflection losses of microwaves passing through the adhesive layer by controlling the dielectric constant and loss of the adhesive layer to be as close as possible to the dielectric constant of the foamed plastic. In particular, for foamed materials with a dielectric constant less than 2.0, the difference in dielectric constant between the adhesive layer and the substrate cannot be ignored in high-frequency and even millimeter-wave bands.

[0013] Preferably, the low dielectric and low loss adhesive layer has a glass transition temperature greater than 240°C.

[0014] In existing technologies, rubber or hydrocarbon rubber is used as the adhesive layer. However, common rubber adhesives, such as butyl rubber and polyisobutyl rubber adhesives, have poor temperature and weather resistance. They are prone to blistering and delamination under long-term high temperature and high humidity conditions, especially in extreme environments. The low-dielectric-loss low-loss adhesive layer of this invention has a glass transition temperature greater than 240 degrees Celsius, which is higher than the glass transition temperature of general cross-linked rubbers and resins. Therefore, the low-dielectric-loss low-loss adhesive layer has better thermal stability.

[0015] Preferably, the low dielectric and low loss adhesive layer has a water absorption rate of less than 0.3% (tested by immersion in water at 50 degrees Celsius for 48 hours).

[0016] The low-dielectric, low-loss adhesive layer has a water absorption rate of less than 0.3%, effectively isolating the metal foil adhesion from changes in environmental humidity and ensuring adhesion stability. Existing technologies, such as epoxy resin, cyanate ester resin, and bismaleimide resin, have water absorption rates exceeding these requirements. For example, cyanate ester resin systems are widely used in radar radome materials, such as BASF's 5575-2, Fiberite's X54-2, Hexcel's HX 1584-3, and Dow Chemical's XU-71787. The 701 cyanate ester resin system developed by the Aerospace Materials and Processes Research Institute has the following process requirements: ε=2.8, tanδ=0.009, Tg=205℃. Its water absorption rate after immersion in water at 22℃ for 40 days is 0.73%, significantly higher than the water absorption rate of the low-dielectric, low-loss adhesive layer described in this invention.

[0017] The low-dielectric-low-loss adhesive layer of this invention has the following possible embodiment. The main component of the low-dielectric-low-loss adhesive layer is one or a mixture of low-loss crosslinked hydrocarbon polymers or low-loss crosslinked polyphenylene ether polymers. The low-loss crosslinked hydrocarbon polymer includes one or more of the following: butadiene polymer, isoprene polymer, butadiene-styrene rubber, butadiene-styrene block polymer, styrene-isoprene block polymer, styrene-isoprene-styrene block polymer, styrene-polybutadiene-styrene block polymer, divinylbenzene polymer, styrene-divinylbenzene polymer, styrene-butadiene-divinylbenzene polymer, ethylene propylene diene monomer (EPDM) rubber, butyl rubber, and cycloolefin polymers (e.g., acenaphthene), crosslinked by free radical initiation. The low-loss crosslinked polyphenylene ether polymer comprises a polyphenylene ether polymer with vinyl or allyl active groups modified on the end groups or side groups of the polymer, crosslinked by free radical initiation.

[0018] Preferably, the low dielectric and low loss adhesive layer may contain fillers or not contain fillers. When fillers are included, the fillers may contain one or a mixture of silica particles, hollow silica, porous silica, hollow glass microspheres, zeolite, molecular sieve, diatomaceous earth, boron nitride, and silicon nitride.

[0019] Preferably, the low dielectric and low loss adhesive layer comprises a reinforcing layer composed of one or two of polytetrafluoroethylene film and polytetrafluoroethylene ceramic composite film, and a resin adhesive layer mainly composed of low loss cross-linked hydrocarbon polymer located on both sides of the reinforcing layer.

[0020] Preferably, the low dielectric and low loss adhesive layer comprises a reinforcing layer composed of a polytetrafluoroethylene film and a resin adhesive layer mainly composed of low-loss cross-linked hydrocarbon polymers located on both sides of the reinforcing layer.

[0021] Preferably, the low-dielectric-low-loss adhesive layer has a thickness of 20 micrometers to 200 micrometers.

[0022] Preferably, the foamed plastic layer comprises one or more of polymethacrylamide foam material, porous / foamed polyimide material, and foamed polyester material.

[0023] Preferably, the foamed plastic layer comprises polymethacrylamide foam material.

[0024] Preferably, the layered structure includes a first metal foil, a second metal foil, a centrally located foamed plastic layer, a first low-dielectric-low-loss adhesive layer located between the first metal foil and the foamed plastic layer, and a second low-dielectric-low-loss adhesive layer located between the second metal foil and the foamed plastic layer. The first low-dielectric-low-loss adhesive layer and the second low-dielectric-low-loss adhesive layer include a reinforcing layer composed of a polytetrafluoroethylene film and resin adhesive layers mainly composed of low-loss cross-linked hydrocarbon polymers located on both sides of the reinforcing layer.

[0025] Preferably, the first and second metal foils are copper foils, the foamed plastic layer is foamed PMI, and the low dielectric and low loss adhesive layer is constructed from a semi-cured adhesive sheet. The semi-cured adhesive sheet is made of a polytetrafluoroethylene film and a resin mainly composed of a low-loss cross-linked hydrocarbon polymer coated on both sides of the polytetrafluoroethylene film.

[0026] As another aspect of this utility model, this utility model also provides a circuit board comprising the above-mentioned low dielectric constant metal foil laminate.

[0027] The advantages of this utility model are: The low dielectric constant metal foil laminate and the circuit board made from the low dielectric constant metal foil laminate of this invention meet the performance requirements of low dielectric constant DK<2.0, low dielectric loss Df<0.005, and metal foil peel strength>3 lbs / inch. It can reduce the refraction and reflection loss of high frequency signals when passing through the interface between the low dielectric and low loss adhesive layer and the foamed plastic layer. It can meet the requirements of strong adhesion between the metal foil and the substrate and long-term reliability of the adhesion, that is, there will be no delamination of the metal foil and the substrate or blistering of the metal foil due to long-term use or the influence of the use environment. Meanwhile, the antenna made using the aforementioned circuit board can effectively increase antenna bandwidth and reduce signal delay, while also improving antenna gain and energy efficiency. This invention contains polytetrafluoroethylene (PTFE) in the low-dielectric, low-loss adhesive layer. By utilizing the excellent chemical inertness of PTFE, it can isolate the influence of the external environment on the low-dielectric substrate, thereby improving the overall weather resistance of the circuit board. Attached Figure Description

[0028] Figure 1 This is an enlarged schematic diagram of the layered structure involved in the embodiment. Detailed Implementation

[0029] The technical solutions of this utility model will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this utility model, and not all of them. Based on the embodiments of this utility model, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this utility model.

[0030] This utility model discloses a low dielectric constant metal foil laminate, which includes at least one metal foil, at least one low dielectric low loss adhesive layer, and at least one foamed plastic layer. At least one low dielectric low loss adhesive layer is disposed between the metal foil and the foamed plastic layer. The metal foil, the low dielectric low loss adhesive layer, and the foamed plastic layer are stacked to form a layered structure.

[0031] Specifically, for the selection of materials for the low-dielectric-low-loss adhesive layer, the main component is limited to one or a mixture of low-loss crosslinked hydrocarbon polymers or low-loss crosslinked polyphenylene ether polymers. Specifically, the low-loss crosslinked hydrocarbon polymer may include one or more of the following: butadiene polymers, isoprene polymers, butadiene-styrene rubber, butadiene-styrene block polymers, styrene-isoprene block polymers, styrene-isoprene-styrene block polymers, styrene-polybutadiene-styrene block polymers, divinylbenzene polymers, styrene-divinylbenzene polymers, styrene-butadiene-divinylbenzene polymers, ethylene propylene diene monomer (EPDM) rubber, butyl rubber, and cyclic olefin polymers, crosslinked by free radical initiation. The low-loss crosslinked polyphenylene ether polymer may be a polyphenylene ether polymer in which the end groups or side groups of the polymer are modified with vinyl or allyl active groups, crosslinked by free radical initiation. In this case, without a reinforcing layer, the dielectric constant of the low-dielectric-low-loss adhesive layer can reach 3.0.

[0032] Regarding the selection of materials for the foamed plastic layer, the foamed plastic layer can be one or more of polymethacrylamide foam material, porous / foamed polyimide material, and foamed polyester material. After the aforementioned material selection, the dielectric constant of the foamed plastic layer can be less than 2.00.

[0033] In existing conventional substrates, the dielectric constant of ordinary adhesive layers is often relatively high (for example, the dielectric constant of ordinary epoxy resin adhesive layers is 3.7-4.0, the dielectric constant of thermosetting PI adhesive layers is 4.0, and the dielectric constant of modified polyphenylene ether and TAIC system adhesive layers is 3.2-3.5). Ordinary substrates use one or more of epoxy resin, polyphenylene ether resin, hydrocarbon resin, BT resin, and polytetrafluoroethylene as the main resin, and their dielectric constant is generally greater than 2.10. Therefore, the dielectric constant and dielectric loss of ordinary substrates are generally high. In this application, the substrate composed of foamed material, i.e., the dielectric constant of the foamed plastic layer, is less than 2.0, and the dielectric constant of the low dielectric and low loss adhesive layer can reach 3.0, which is close to the dielectric constant of the foamed material. Thus, the low dielectric constant metal foil laminate obtained can meet the performance requirements of low dielectric constant (DK<2.0) and low dielectric loss (Df<0.005).

[0034] However, when using high dielectric constant bonding layers in existing technologies, the actual test results of the fabricated microwave devices often differ significantly from the simulation results. For example, when using foamed plastic to fabricate Luneburg lenses, the epoxy resin bonding leads to the above-mentioned problems. The main reason is that the large difference in dielectric constant between the bonding layer resin and the foam layer results in microwave refraction and reflection losses. (YAN Xiulin, SHI Yunqi, ZHU Lina. Design of Luneburg Lens Antenna Based on Novel Foam Materials[J]. Journal of Electronics&Information Technology, 2022,44(12): 4111-4115. doi: 10.11999 / JEIT220569).

[0035] In this application, the metal foil can be selected from one or more of copper foil, aluminum foil, stainless steel, and embedded copper foil, and the thickness is limited so that the thickness of the metal foil is from 8 micrometers to 200 micrometers.

[0036] Regarding the low dielectric and low loss adhesive layer, the thickness is limited to 20 micrometers to 200 micrometers.

[0037] In this disclosure, the structure and materials of the low-dielectric-low-loss adhesive layer have been optimized. Specifically, the low-dielectric-low-loss adhesive layer further comprises a reinforcing layer composed of one or two of polytetrafluoroethylene (PTFE) films and PTFE-ceramic composite films. That is, the low-dielectric-low-loss adhesive layer also includes a reinforcing material, which is one or two of PTFE films and PTFE-ceramic composite films.

[0038] By incorporating polytetrafluoroethylene (PTFE), a reinforcing material, into the low-dielectric-loss adhesive layer, the PTFE can lower the dielectric constant of the low-dielectric-loss adhesive layer from 3.0 to approximately 2.7. This further reduces the difference in dielectric constant between the low-dielectric-loss adhesive layer and the foamed plastic layer (DK<2), resulting in lower microwave refraction. Simultaneously, the excellent chemical inertness of PTFE isolates the low-dielectric substrate from external environmental influences, thereby improving the overall weather resistance of the circuit board.

[0039] In this application, the dielectric loss of the low dielectric and low loss adhesive layer at a frequency of 10 GHz can reach less than 0.0040, the glass transition temperature of the low dielectric and low loss adhesive layer is greater than 240°C, and the water absorption rate of the low dielectric and low loss adhesive layer is less than 0.3% (tested by immersion in water at 50°C for 48 hours).

[0040] It should be noted that in existing technologies, rubber or hydrocarbon rubber is used as the adhesive layer. However, ordinary rubber adhesives, such as butyl rubber and polyisobutyl rubber adhesives, have poor temperature and weather resistance, and are prone to blistering and delamination under long-term high temperature and high humidity use, especially in extreme environments. In contrast, the low-dielectric-loss adhesive layer described in this invention has a glass transition temperature greater than 240 degrees Celsius, which is higher than the glass transition temperature of general cross-linked rubbers and resins. Therefore, the low-dielectric-loss adhesive layer in this disclosure has better thermal stability.

[0041] In this disclosure, the water absorption rate of the low-dielectric-low-loss adhesive layer is less than 0.3%, which effectively isolates the influence of environmental humidity changes on the metal foil adhesion and ensures adhesion stability. In contrast, the water absorption rates of existing technologies, such as epoxy resin adhesive layers, cyanate ester resin adhesive layers, and bismaleimide resin adhesive layers, are all higher than the above requirements. For example, cyanate ester resin systems are widely used in the wave-transparent materials of radomes, such as BASF's 5575-2, Fiberite's X54-2, Hexcel's HX 1584-3, and Dow Chemical's XU-71787. The 701 cyanate ester resin system developed by the Aerospace Materials and Processes Research Institute has the following process requirements: ε=2.8, tanδ=0.009, Tg=205℃, and a water absorption rate of 0.73% after immersion in water at 22℃ for 40 days, which is significantly higher than the water absorption rate of the low-dielectric-low-loss adhesive layer described in this invention.

[0042] The following detailed embodiment illustrates the specific preparation method of the low dielectric constant metal-coated laminate, which includes the following steps: S1. Prepare a low-dielectric-low-loss adhesive layer; S2. Place the low dielectric and low loss adhesive layer between the metal foil and the foamed plastic layer to form a multi-layer structure; S3. Place the above multi-layer structure in a laminator or molding machine. Under certain temperature and pressure, the adhesive layer cross-links, and at the same time, the metal foil and the foamed plastic layer are bonded together.

[0043] In this embodiment, the method for preparing the low dielectric and low loss adhesive layer described in S1 can be exemplified as follows: For example, a dip coating method can be used, in which a resin, initiator, filler, and other composition are selected as the main body of a low-loss crosslinked hydrocarbon polymer or a low-loss crosslinked polyphenylene ether polymer as the main body, and the slurry is prepared and coated on both sides of a polytetrafluoroethylene film and / or a polytetrafluoroethylene ceramic composite film. The solvent is removed, and partial curing occurs to form a semi-cured adhesive sheet, which can be used as the adhesive material for the low dielectric and low loss adhesive layer.

[0044] It should be noted that in this embodiment: a low-loss cross-linked hydrocarbon polymer was selected as the main resin to manufacture the semi-cured adhesive sheet, specifically the applicant's self-developed HM270B semi-cured adhesive sheet, with a thickness of 110 micrometers. This semi-cured adhesive sheet contains a reinforcing material, which is a polytetrafluoroethylene film. A resin based on a low-loss cross-linked hydrocarbon polymer is coated on both sides of the reinforcing material. Its dielectric constant is 2.7 at 10 GHz, its dielectric loss is 0.0020 at 10 GHz, its glass transition temperature is greater than 280 degrees Celsius (resin layer), and its water absorption rate is 0.07% (50 degrees Celsius, 48h). The metal foil used is TWL-HP 1 oz copper foil from Luxembourg Circuit Copper Foil Factory. The foamed plastic layer is made of foamed PMI foam board, specifically the ROHACELL 71HF from Evonik Industries AG, with a thickness of 2.0 mm.

[0045] The temperature in S3 must meet the following two conditions: (A) it can initiate the cross-linking reaction of the low dielectric and low loss adhesive layer; (B) it will not cause irreversible deformation of the foamed plastic layer.

[0046] The pressure described in S3 is not limited in this invention, provided that it can effectively bond the material without causing irreversible deformation of the foamed plastic layer.

[0047] Meanwhile, crosslinking and bonding can be carried out within the range of temperature: 80℃~300℃, pressure: 0.1kg / cm²~200kg / cm², and time: 1 minute~10 hours. More preferably, it can be carried out within the range of temperature: 150℃~250℃, pressure: 1kg / cm²~30kg / cm², and time: 1 minute~2 hours.

[0048] The low dielectric constant metal foil laminate prepared by the above method can also be used to manufacture electrical and electronic components. Specifically, circuit boards can also be made using the low dielectric constant metal foil laminate as raw material.

[0049] The low dielectric constant metal foil laminate is described below with a specific layered structure. The low dielectric constant metal foil laminate is plate-shaped and has a metal foil, a low dielectric low loss adhesive layer, and a foamed plastic layer. The metal foil, the low dielectric low loss adhesive layer, and the foamed plastic layer are stacked to form a layered structure. The low dielectric low loss adhesive layer has a reinforcing layer composed of one or two of polytetrafluoroethylene film and polytetrafluoroethylene ceramic composite film.

[0050] Specifically, refer to Figure 1 In this embodiment, the layered structure includes a first metal foil 1, a second metal foil 2, a centrally located foamed plastic layer 3, a first low-dielectric-low-loss adhesive layer 4 located between the first metal foil 1 and the foamed plastic layer 3, and a second low-dielectric-low-loss adhesive layer 5 located between the second metal foil 2 and the foamed plastic layer 3. The first low-dielectric-low-loss adhesive layer 4 and the second low-dielectric-low-loss adhesive layer 5 each include a polytetrafluoroethylene (PTFE) film reinforcement layer 6 and resin adhesive layers 7, primarily composed of low-loss cross-linked hydrocarbon polymers, located on both sides of the PTFE film reinforcement layer 6. In actual production, the resin primarily composed of low-loss cross-linked hydrocarbon polymers is coated on both sides of the PTFE film to create a semi-cured adhesive sheet, which serves as the adhesive material for the low-dielectric-low-loss adhesive layer.

[0051] In this embodiment, the selection of materials for the metal foil, foamed plastic layer, and low-dielectric-low-loss adhesive layer is as follows: the first metal foil 1 and the second metal foil 2 are both copper foils; the foamed plastic layer 3 is foamed PMI (DK<2); the first low-dielectric-low-loss adhesive layer 4 and the second low-dielectric-low-loss adhesive layer 5 are both semi-cured adhesive sheets made of low-loss cross-linked hydrocarbon polymer as the main resin. The semi-cured adhesive sheet contains a reinforcing material—polytetrafluoroethylene (PTFE), which is presented as a PTFE film, while the resin based on the low-loss cross-linked hydrocarbon polymer is coated on both sides of the PTFE film.

[0052] The aforementioned layered structure was placed in a vacuum laminator at a pressure of 0.4 MPa, a temperature of 190°C, and a lamination time of 30 minutes to obtain a low-dielectric material substrate. The low-dielectric material substrate was tested using the IPC-TM-650 2.5.5.5 method. At a frequency of 10 GHz, the dielectric constant and dielectric loss were DK=1.26 and Df=0.0029, respectively. Using the GB / T 4722 7.2 method, the copper foil peel strength in the receiving state was tested to be P / S=4.1 lbs / inch. After undergoing a 96-hour high-low temperature cycling test (-40°C to 80°C), the copper foil did not delaminate or blister, and the peel strength remained at P / S=4.1 lbs / inch, showing no loss in peel strength.

[0053] The above description is only a preferred embodiment of this utility model and does not limit the patent scope of this utility model. All equivalent structural transformations made under the practical concept of this utility model using the contents of this utility model specification and drawings, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this utility model.

Claims

1. A low dielectric constant metal foil laminate, characterized in that, include: The structure comprises at least one metal foil, at least one low-dielectric-low-loss adhesive layer, and at least one foamed plastic layer, wherein at least one low-dielectric-low-loss adhesive layer is disposed between the metal foil and the foamed plastic layer; the metal foil, the low-dielectric-low-loss adhesive layer, and the foamed plastic layer are stacked to form a layered structure, wherein the low-dielectric-low-loss adhesive layer has a reinforcing layer composed of one or two of polytetrafluoroethylene film and polytetrafluoroethylene ceramic composite film.

2. The low dielectric constant metal foil laminate as described in claim 1, characterized in that: The metal foil includes one of copper foil, aluminum foil, and stainless steel; the thickness of the metal foil is from 8 micrometers to 200 micrometers.

3. The low dielectric constant metal foil laminate as described in claim 1, characterized in that: The layered structure has a dielectric constant DK < 2.0, a dielectric loss Df < 0.005, and a metal foil peel strength > 3 lbs / inch. The dielectric constant of the low-dielectric-low-loss adhesive layer is between 2.0 and 2.8, the dielectric loss Df < 0.004, the glass transition temperature Tg > 240℃, and the water absorption rate is less than 0.3%.

4. The low dielectric constant metal foil laminate as described in claim 3, characterized in that: The low dielectric and low loss adhesive layer is mainly composed of a low-loss cross-linked hydrocarbon polymer.

5. The low dielectric constant metal foil laminate as described in claim 3, characterized in that: The low dielectric and low loss adhesive layer The main component is a low-loss cross-linked polyphenylene ether polymer; The low-loss crosslinked polyphenylene ether polymer comprises a polyphenylene ether polymer with vinyl or allyl active groups modified on the end groups or side groups of the polymer, which is then crosslinked by free radical initiation.

6. The low dielectric constant metal foil laminate as described in claim 4 or 5, characterized in that: The low dielectric and low loss adhesive layer includes a reinforcing layer composed of one or two of polytetrafluoroethylene film and polytetrafluoroethylene ceramic composite film, and a resin adhesive layer mainly composed of low loss cross-linked hydrocarbon polymer located on both sides of the reinforcing layer. The low dielectric and low loss adhesive layer includes a reinforcing layer composed of a polytetrafluoroethylene film and a resin adhesive layer on both sides of the reinforcing layer, which is mainly composed of low-loss cross-linked hydrocarbon polymers.

7. The low dielectric constant metal foil laminate as described in claim 6, characterized in that: The low-dielectric, low-loss adhesive layer has a thickness of 20 micrometers to 200 micrometers.

8. The low dielectric constant metal foil laminate as described in claim 6, characterized in that: The foamed plastic layer has a dielectric constant of less than 2.0; the foamed plastic layer comprises one of polymethacrylamide foam material, porous / foamed polyimide material, and foamed polyester material.

9. The low dielectric constant metal foil laminate as described in claim 8, characterized in that: The layered structure includes a first metal foil, a second metal foil, a centrally located foamed plastic layer, a first low-dielectric-low-loss adhesive layer between the first metal foil and the foamed plastic layer, and a second low-dielectric-low-loss adhesive layer between the second metal foil and the foamed plastic layer. The first and second low-dielectric-low-loss adhesive layers include a reinforcing layer made of polytetrafluoroethylene film and resin adhesive layers on both sides of the reinforcing layer, which are mainly composed of low-loss cross-linked hydrocarbon polymers.

10. The low dielectric constant metal foil laminate as described in claim 9, characterized in that: The first and second metal foils are copper foils, the foamed plastic layer is foamed PMI, and the low dielectric and low loss adhesive layer is constructed from a semi-cured adhesive sheet. The semi-cured adhesive sheet is made of a polytetrafluoroethylene film and a resin mainly composed of a low-loss cross-linked hydrocarbon polymer coated on both sides of the polytetrafluoroethylene film.

11. A circuit board, characterized in that, The low dielectric constant metal foil laminate includes any one of claims 1-10.